Communicating across tourism silos for inclusive sustainable partnerships. Issue 9 (2nd September 2018) - Cockburn-Wootten, Cheryl; McIntosh, Alison J.; Smith, Kim; Jefferies, Sharon
Abstract: Overcoming traditional tourism silos to develop long-term relationships with stakeholders is essential for transformational change. Adopting broader networks connects researchers to pertinent issues facing society, develops reciprocal capacities for learning, and creates inclusive sustainable partnerships. As critical tourism scholars and not-for-profit employees, we illustrate the journey of how we engaged collaboratively with diverse stakeholders, from businesses, not-for-profits and the university, to tackle issues of economic disadvantage and social exclusion. Critical hospitality and dialogue theory were adopted to provide a framework for the processes of collaboration, research, networking, and advocacy work for inclusive sustainable spaces. Drawing on our involvement with co-founding a collaborative research network, the Network for Community Hospitality, and analysis of data from two Ketso workshops and interviews with 41 network members, we present reflections on setting up and facilitating the network. In addition, two examples of collaborative Network activities are presented to illustrate the techniques and dialogic communication processes for doing critical hospitality. The article thereby contributes by providing empirically informed and reflexive understandings into the experiences of working and communicating within long-term inclusive partnerships with diverse stakeholders to create traction for positive social sustainable change.